HIGH SCHOOL TEACHERS’ ATTITUDES TO INTEGRATE THE SUSTAINABLE DEVELOPMENT GOALS INTO ENGLISH EDUCATION: AN EMPIRICAL STUDY FROM CHINA - Yiran Wei; Nor Asniza Ishak (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study aims to investigate Chinese high school teachers’ attitudes toward integrating the SDGs into English education and examine whether there are differences in terms of gender, age, teaching experience, and professional titles. The study adopted an online purposive sampling survey method and collected 400 questionnaire data, including 381 valid questionnaires. The collected data were analysed using the descriptive and differential analysis methods of SPSS 27. The results found that teachers have lower attitudes towards integrating the SDGs into English education (mean =3.30), with the average score of cognitive attitudes being higher than behavioural attitudes. The overall attitude of female teachers is higher than that of male teachers, that of younger teachers is higher than that of older teachers, and that of teachers with 11-20 years of teaching experience and intermediate professional titles is higher than that of the other two groups. The difference analysis shows that teachers’ cognition, behaviour and overall attitude are significantly affected by teaching experience and age, while gender and professional title have little impact on attitudes. Respondents generally cited a lack of understanding of the SDGs and a lack of relevant training and support. Finally, the researchers proposed four suggestions to integrate SDGs into English education effectively.